ANALISIS PERUBAHAN LAJU TEMPERATUR TUNGKU FORGING PORTABLE DENGAN PEMBESARAN 5 CM BUKAAN LUBANG PEMBAKARAN - Ongki Prima Widodo; Armila Armila; Rudi Kurniawan Arief (Ensiklopedia Research and Community Service Review, 2022)
A metallurgical furnace is needed in the metal forming process, a portable forging furnace is an installation tool specifically designed for metal heating, for the plastic deformation process in the forging process in the material technology laboratory. This heating furnace was made by Feriadi Sidik with an initial opening of 50 mm diameter, only capable of reaching a temperature of 3000C with a hole position of 15:85 cm. the inability of this furnace to reach temperatures greater than 10000C which causes the practicum process to be hampered, therefore modifications were made by widening the combustion opening from 50 mm to 100 mm. Enlargement of these openings results in a change in compressor pressure which results in a change in the air flow rate so that the temperature propagates up. The increase in temperature is measured from changes in the compressor speed and the resulting temperature at the initial pressure (P= 17.2km/h, T= 309.20C), and the final pressure (P=23.2km/h, T= 14320C), with testing time for from 30 seconds to 300 seconds. From the modification results, it is proven that by increasing the opening of the combustion hole, it can produce a change in the temperature rate. This modified furnace can be used to heat low carbon steel and high carbon steel for the forging process. Keywords: Furnace, Modification, Forging, Temperature, openings